2018
DOI: 10.3102/0013189x18769302
|View full text |Cite
|
Sign up to set email alerts
|

Short Comparative Interrupted Time Series Using Aggregate School-Level Data in Education Research

Abstract: Short comparative interrupted times series (CITS) designs are increasingly being used in education research to assess the effectiveness of school-level interventions. These designs can be implemented relatively inexpensively, often drawing on publicly available data on aggregate school performance. However, the validity of this approach hinges on a variety of assumptions and design decisions that are not clearly outlined in the literature. This article aims to serve as a practice guide for applied researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Here, we employ comparative interrupted time series (CITS) design, a quasi-experimental research method to explore the policy impact with controls for observed and unobserved differences between states and common time trends (Hallberg et al, 2018). CITS allows us to use repeated measures of principals’ goal priorities and compare pre-NCLB and post-NCLB trends between the two groups of states.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we employ comparative interrupted time series (CITS) design, a quasi-experimental research method to explore the policy impact with controls for observed and unobserved differences between states and common time trends (Hallberg et al, 2018). CITS allows us to use repeated measures of principals’ goal priorities and compare pre-NCLB and post-NCLB trends between the two groups of states.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that do not separate the results by a specific turnaround model or specify which turnaround model was implemented but otherwise followed our definition of school turnaround are included in an inclusive category. For instance, if a study examines how school transformation and turnaround both influence student outcomes, then we would classify these estimates in the general category (i.e., Hallberg et al, 2018; Sun et al, 2017). To understand whether a change in management or governance is associated with improved student outcomes, we compare schools that maintained local control during their turnaround process to restart schools and schools that were taken over by the state (i.e., Recovery School District; Achievement School District).…”
Section: Methodsmentioning
confidence: 99%
“…Several options exist for matching comparison cases with treatment cases in education research, but the relatively small proportion of IB schools in the United States (i.e., <2% of all public schools) prompted us to use a nearest neighbor 1:1 match. That choice avoided computational and interpretive challenges that can come from highly unbalanced designs, which would have been likely had we matched each IB school against multiple comparison schools (Hallberg et al, 2018; Keppel & Wickens, 2004). That choice did not, meanwhile, thwart our identification of comparisons that best approximated our data set’s schools, which opted to offer IB (Hallberg et al, 2018; Jacob et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…That choice avoided computational and interpretive challenges that can come from highly unbalanced designs, which would have been likely had we matched each IB school against multiple comparison schools (Hallberg et al, 2018; Keppel & Wickens, 2004). That choice did not, meanwhile, thwart our identification of comparisons that best approximated our data set’s schools, which opted to offer IB (Hallberg et al, 2018; Jacob et al, 2016). We expected observable factors, not randomness, to associate with whether a school adopted an IB program, so our matching approach adhered to logic from research on IB access that advocates for controlling the type of self-selection that can plagues IB studies (May et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation